C=C insertion over N=C=O of allyl isocyanate into the Ge-Si bond of a germylene - Ajithkumar, V. S.; Khilari, Nripen; Ghanwat, Pratiksha B.; Koley, Debasis; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2025)
Two isocyanates are reacted with the germylene, PhC(NtBu)(2)Ge-Si(SiMe3)(3) (1). Phenyl isocyanate undergoes catalytic cyclotrimerization with 1 leading to 1,3,5-triphenyl isocyanurate (2), while allyl isocyanate undergoes both cyclotrimerization and the C=C bond insertion between the Ge-Si bond. The constitution of 3 is determined by single-crystal X-ray studies. The contrasting reactivity pattern is explained by comprehensive density functional theory studies.
Keywords: Cyclotrimerization; Density functional theory; Germylene; Insertion; isocyanates